Reconnaissance of selected PPCP compounds in Costa Rican surface waters - Spongberg, Alison L. (2011)
Eighty-six water samples were collected in early 2009 from Costa Rican surface water and coastal locations for the analysis of 34 pharmaceutical and personal care product compounds (PPCPs). Sampling sites included areas receiving treated and untreated wastewaters, and urban and rural runoff. PPCPs were analyzed using a combination of solid phase extraction and liquid chromatography tandem mass spectrometry. The five most frequently detected compounds were doxycycline (77%), sulfadimethoxine (43%), salicylic acid (41%), triclosan (34%) and caffeine (29%). Caffeine had the maximum concentration of 1.1 mg L 1 , possibly due to coffee bean production facilities upstream. Other compounds found in high concentrations include: doxycycline (74 mg L 1 ), ibuprofen (37 mg L 1 ), gemfibrozil (17 mg L 1 ), acetominophen (13 mg L 1 ) and ketoprofen (10 mg L 1 ). The wastewater effluent collected from an oxidation pond had similar detection and concentrations of compounds compared to other studies reported in the literature. Waters receiving runoff from a nearby hospital showed higher concentrations than other areas for many PPCPs. Both caffeine and carbamazepine were found in low frequency compared to other studies, likely due to enhanced degradation and low usage, respectively. Overall concentrations of PPCPs in surface waters of Costa Rica are inline with currently reported occurrence data from around the world, with the exception of doxycycline